Millions Fed: Proven successes in agricultural development - Spielman, David J.; Pandya-Lorch, Rajul (International Food Policy Research Institute, 2009)
Learning from successes in agricultural development is now more urgent than ever. Progress in feeding the world’s billions has slowed, while the challenge of meeting future food needs remains enormous and is subject to new uncertainties in the global food and agricultural systems. In the late 1950s around a billion people were estimated to go hungry every day. Scientists, policymakers, farmers, and ordinary people initiated a concerted push to boost agricultural production and productivity in developing countries. Great strides were also made in improving the quality of food and the ability of vulnerable people to access food needed for survival. All these efforts have done more than just feed millions. They have also demonstrated that agriculture can be a key driver of growth and development for many of the world’s poorest countries.